Model of the Automated Warehouse Management and Forecasting System in the Conditions of Transition to Industry 4.0. Issue 13 (2019) - Lototsky, V.; Sabitov, R.; Smirnova, G.; Sirazetdinov, B.; Elizarova, N.; Sabitov, Sh.
Abstract: Dynamic model of the automated warehouse management and forecasting system in the conditions of Industry 4.0 is discussed. Usage of inductive knowledge base allows to predict the appearance of bottlenecks in advance and actually turns the warehouse management system into an expert with all the necessary integral experience, which helps to reduce significantly the financial costs of excessive inventory and to prevent certain components shortage possibility.